Sports-related sudden cardiac arrest in young adults. Issue 2 (18th October 2022) - Bohm, Philipp; Meyer, Tim; Narayanan, Kumar; Schindler, Matthias; Weizman, Orianne; Beganton, Frankie; Schmied, Christian; Bougouin, Wulfran; Barra, Sergio; Dumas, Florence; Varenne, Olivier; Cariou, Alain; et al.
Abstract: Aims: Data on sports-related sudden cardiac arrest (SrSCA) among young adults in the general population are scarce. We aimed to determine the overall SrSCA incidence, characteristics, and outcomes in young adults. Methods and results: Prospective cohort study of all cases of SrSCA between 2012 and 2019 in Germany and Paris area, France, involving subjects aged 18–35 years. Detection of SrSCA was achieved via multiple sources, including emergency medical services (EMS) reporting and web-based screening of media releases. Cases and aetiologies were centrally adjudicated. Overall, a total of 147 SrSCA (mean age 28.1 ± 4.8 years, 95.2% males) occurred, with an overall burden of 4.77 [95% confidence interval (CI) 2.85–6.68] cases per million-year, including 12 (8.2%) cases in young competitive athletes. While bystander cardiopulmonary resuscitation (CPR) was initiated in 114 (82.6%), automated external defibrillator (AED) use by bystanders occurred only in a minority (7.5%). Public AED use prior to EMS arrival (odds ratio 6.25, 95% CI 1.48–43.20, P = 0.02) was the strongest independent predictor of survival at hospital discharge (38.1%). Among cases that benefited from both immediate bystander CPR and AED use, survival rate was 90.9%. Coronary artery disease was the most frequent aetiology (25.8%), mainly through acute coronary syndrome (86.9%). Conclusion: Sports-related sudden cardiac arrest in the young occurs mainly in recreational male sports participants. Public AED use remains disappointingly low, although survival may reach 90% among those who benefit from both bystander CPR and early defibrillation. Coronary artery disease is the most prevalent cause of SrSCA in young adults.